Rational design of graphene-based architectures for high-performance lithium-ion battery anodes - Wang, Huan (Kansas State University, 2018)
Advances in synthesis and processing of nanocarbon materials, particularly graphene, have presented the opportunity to design novel Li-ion battery (LIB) anode materials that can meet the power requirements of next-generation power devices. This thesis presents three studies on electrochemical behavior of three-dimensional (3D) nanostructured anode materials formed by pure graphene sheets and graphene sheets coupled with conversion active materials (metal oxides). In the first project, a microgel-templated approach for fabrication of 3D macro/mesoporous reduced graphene oxide (RGO) anode is discussed. The mesoporous 3D structure provides a large specific surface area, while the macropores also shorten the transport length of Li ions. The second project involves the use of a novel magnetic field-induced method for fabrication of wrinkled Fe₃O₄@RGO anode materials. The applied magnetic field improves the interfacial contact between the anode and current collector and increases the stacking density of the active material. The magnetic field treatment facilitates the kinetics of Li ions and electrons and improves electrode durability and the surface area of the active material. In the third project, poly (methacrylic acid) (PMAA)-induced self-assembly process was used to design super-mesoporous Fe₃O₄@RGO anode materials and their electrochemical performance as anode materials is also investigated. To establish correlations between electrode properties (morphological and chemical) and LIB performance, a variety of techniques were used to characterize the samples. The significant improvement in LIB performance of the 3D anodes mentioned above is largely attributed to the unique properties of graphene and the resulting 3D architecture.
Keywords: Lithium-ion battery